Decoupling Taxes and Marriage: Beyond Innocence and Income Splitting - Drumbl, Michelle Lyon (Columbia Journal of Tax Law, 2013)
Fourteen years ago, members of Congress sympathetically listened as divorcees testified to their struggles to raise children while being pursued by the Internal Revenue Service for tax debts, often unknown to them, that were attributable to their ex-husbands’ income. Rather than adopting one of many proposals to end joint and several liability, Congress instead elected to expand the grounds on which these individuals could seek relief from such liability. Since that time, taxpayers have seen a steady expansion of the grounds for so-called “innocent spouse relief” that has evolved through a combination of legislative, administrative, and judicial action. Yet the process for relief remains time-consuming, inefficient, and unpredictable. The majority of initial requests for innocent spouse relief are denied. The taxpayer can appeal administratively and also seek judicial review if relief is denied, but sometimes will spend several years and untold resources in pursuit of a claim that may ultimately be unsuccessful. The process is also a questionable use of Internal Revenue Service personnel, in that it frequently calls upon these employees to address the most intimate aspects of a failed relationship, including spousal abuse, addictions, and mental health problems. These employees often must make a determination based upon a “he-said, she-said” presentation of the facts—an odd task for an agency charged with enforcing the revenue laws. This article visits the historic rationales for joint and several liability, both in light of the flawed relief process and also in the context of modern-day American society, in which married couples constitute only half of all households and cohabitation is increasingly more common. I conclude that Congress should eliminate the “married” filing statuses and require each married individual to file a separate return. If it did so, joint liability and the innocent spouse relief process would both cease to exist. The historical policy justifications for imposing joint and several liability are no longer rational in light of changed demographics and technological advances. Rather than an “unusual privilege,” which it was long said to be, filing jointly has become a risky conundrum, particularly for low-income taxpayers. As the nation debates tax reform, it is appropriate to rethink the policy of retaining the “married” filing statuses in light of the ways in which family structures, society, and the Internal Revenue Code have changed since joint and several liability was introduced in 1938.